Retention strategies for medical doctors in low- and middle-income countries (LMICs): are they effective? A scoping review - Norehan Jinah; Izzuan Khirman Adnan; Pangie Bakit; Ili Abdullah Sharin; Kun Yun Lee (BMC Health Services Research)
Abstract Background High turnover among the medical professions is detrimental to the healthcare system and population well-being, particularly in low- and middle-income countries (LMICs) with limited financial and human resources. To prevent brain drain, effective strategies are vital to improve the retention of healthcare workers, especially doctors. However, little evidence has been synthesised regarding the effectiveness of these strategies, especially in LMICs. This scoping review aimed to evaluate the retention strategies implemented in LMICs and their effectiveness in mitigating doctor turnover. Methods Four databases; MEDLINE (PubMed), Scopus, ScienceDirect, and EBSCOHost were searched using pre-determined keywords to identify articles published between January 1st, 2013 and February 28th, 2023 that evaluated retention strategies for doctors in LMICs. The review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses-Extension for Scoping Reviews (PRISMA-ScR) guidelines to ensure transparency. Relevant studies were identified, screened, and narratively synthesised. Results Thirteen articles were included, representing a diverse range of LMICs. Retention strategies were categorised into educational, financial incentives, regulatory, as well as professional and personal support. Approximately 77% (n = 10) of studies reported positive outcomes, another two did not achieve favourable results, while one showed mixed outcomes. An equal number of studies applying single-strategy (n = 5) and combined-strategy (n = 5) approaches reported successful outcomes, especially when focusing on education and/ or regulatory strategies. More notably, international collaboration in education strategies enhanced success rates while compulsory service enforcement by authorities helped retain doctors in underserved areas to address healthcare worker maldistribution. Efficiency in administrative management, regardless of urban or rural locations, also emerged as a key factor of successful retention. Conclusions This review highlighted the effectiveness of different retention strategies for doctors in LMICs and its associated factors. It is imperative to emphasise the lack of a one-size-fits-all solution for this global issue. Thus, a multifaceted, comprehensive approach is essential in producing sustainable health workforce development that ensures optimal health outcomes, especially for populations in underserved areas. Future studies should prioritise pre- and post-intervention comparisons using appropriate indicators to enhance understanding and guide effective interventions for doctor retention.